Rancang Bangun Aplikasi Pengecekan Dokumen Digital Tugas Mahasiswa Berbasis Website - Haeruddin Haeruddin; Gunawan Putra Wahdana; Dhimas Tribuana; Dayanti Dayanti; Nur Inda (Jurnal Teknologi dan Bisnis Cerdas, 2026)
The development of information technology has encouraged the submission of student assignments to shift from physical documents to digital documents. However, this convenience also creates new challenges, such as unstructured assignment archiving and the increasing potential for document similarity among students. This study aims to design and develop a website-based digital document checking application for student assignments that can manage documents and automatically display similarity percentages between files. The system was developed using the Waterfall method through requirement analysis, system design, implementation, testing, and evaluation stages. The technologies used include HTML, CSS, PHP, JavaScript, MySQL, XAMPP, and Sublime Text. The document checking process consists of document upload, text extraction, text preprocessing, word weighting using TF-IDF, and similarity measurement using the cosine similarity method. The data used consisted of 165 student assignment files, comprising 79 dataset files and 86 test files. Testing on five sample documents showed that the system was able to display various similarity percentages of 5%, 12%, 45%, 88%, and 92%, categorized as original, plagiarism indication, and high plagiarism. These results indicate that the application can assist lecturers in conducting an initial examination of similarity in student assignment documents. Therefore, the developed application has the potential to support more effective academic document management and improve academic integrity in higher education environments.